ANALISIS PRAKTIK SUSTAINABLE FASHION PADA BRAND SEJAUH MATA MEMANDANG - Larissa, Tiara; Titisari, Bintan (Jurusan Seni Rupa ISBI Bandung, 2022)
The aspect of sustainability is currently something that needs to be considered for fashion brands in Indonesia. Apart from the unresolved problems of fast fashion, paying attention to the sustainability aspect can have a positive impact in various aspects, starting from the local economy, reducing the use of toxic materials, and being able to give a big impact by participating in saving planet earth. In Indonesiaf, sustainability aspect can be adapted with an approach that refers to the cultural aspect, because Indonesia is rich in traditions from various regions, this can be a strategic step in achieving sustainability from various aspects. This research uses a descriptive qualitative method by making the brand Sejauh Mata Memandang as a case study. Sejauh Mata Memandang is a brand from Indonesia that focuses on fashion products with batik techniques. The data was taken through a literature study and analyzed based on a sustainable fashion model by describing each aspect referrs to the practices that carried out by the brand as far as the eye can see. the results are obtained in the form of conclusions on how the sustainable fashion approach can run from every aspect of sustainability based on the practices that have been applied by the Sejauh Mata Memandang.Keywords: Sustainable fashion, Fashion Brand, Sustainable Practice, Sejauh Mata Memandang———————————————————————————-Aspek sustainability saat ini menjadi hal yang perlu diperhatikan bagi fashion brand di Indonesia. Selain karena permasalahan dari fast fashion yang tidak kunjung terselesaikan, memperhatikan aspek sustainability dapat menghadirkan dampak positif dalam berbagai aspek, mulai dari jalannya ekonomi lokal, berkurangnya penggunaan toxic material, hingga dapat memberi impact yang besar dengan ikut serta dalam penyelamatan planet bumi. Di Indonesia sendiri, aspek sustainability dapat diadaptasi dengan pendekatan yang mengacu pada aspek kultural, karena Indonesia yang kaya akan tradisi dari berbagai daerah, hal ini dapat menjadi langkah strategis dalam mencapai sustainability dari berbagai aspek. Penelitian ini menggunakan metode kualitatif deskriptif dengan menjadikan brand Sejauh Mata Memandang sebagai studi kasus. Sejauh Mata Memandang adalah brand asal Indonesia yang fokus pada produk fashion dengan teknik batik. Data diambil melalui studi literatur dan dianalisis berdasarkan model sustainable fashion dengan mengurai masing- masing aspek mengacu pada praktik yang sudah dijalankan oleh brand Sejauh Mata Memandang. Sehingga didapat hasil berupa simpulan bagaimana pendekatan sustainable fashion dapat berjalan dari setiap aspek sustainability berdasarkan praktik yang sudah diterapkan oleh brand Sejauh Mata Memandang.Kata kunci: Fashion Berkelanjutan, Fashion Brand, Praktik Sustaianable, Sejauh Mata Memandang